Mitigating Acute Climate Change Threats to Reintroduced Migratory Northern Bald Ibises - Johannes Fritz; Markus Unsoeld; Bernhard Goenner; Regina Kramer; Lisbet Siebert-Lang; Helena Wehner (Conservation)
For the past 20 years, reintroduction efforts have been underway to re-establish a migratory population of Northern Bald Ibises (Geronticus eremita) in Central Europe, which now consists of more than 250 birds. They breed both north and south of the Alps and migrate to a common wintering ground in Tuscany. Recently, the start of autumn migration has been increasingly delayed, which correlates with extended warm periods in autumn. Later in the year, however, the birds no longer find sufficient thermals to cross the Alps and remain in the northern Alpine foothills. In order to save their lives, we had to capture the affected birds before the onset of winter, which is not a sustainable solution. A new approach to solving the problem is the establishment of a second migration route to a wintering area in Andalusia, Spain, connecting our population with a sedentary population there. The new migration route bypasses mountain barriers and also allows the birds to reach the wintering grounds later in the year. The modelling of a pan-European population will provide the birds with high ecological and spatial flexibility. Our project exemplifies the consequences of advancing global warming for animal populations and the associated challenges for conservation projects.